Anthropology - Haviland, William A. (New York : Holt, Rinehart and Winston, Inc., 1974)
This text is designed for introductory anthropology courses at the college level.
Part 1. The study of man -- Part 2. The evolution of man -- Part 3. The archeological record -- Part 4. Culture and man -- Part 5. The formation of groups -- Part 6. Social integration -- Part 7. Change and the future.
Includes bibliographical references and index.
Keywords: ANTHROPOLOGY